State of the World’s Indigenous Peoples - United Nations (United Nations, 2019)
On 13 September 2007, the United Nations General Assembly adopted the United Nations Declaration on the Rights of Indigenous Peoples. It marked the culmination of decades of struggle among indigenous peoples for a universal framework establishing minimum standards to ensure the survival, dignity and well-being of the indigenous peoples of the world. This publication looks back at ten-plus years of the Declaration’s existence—more than ten years both of implementation and progress and of unfulfilled expectations.